Fungal Exopolymeric Substances and Their Applications - Topal, Murat; Arslan Topal, E. Işıl (Springer Nature, 2022)
Exopolymeric substances that are also known as extracellular polymeric substances, extracellular polysaccharides, exopolymers, and exopolysaccharides are produced by various microorganisms. They primarily include polysaccharides, lipids, nucleic acids, and proteins. Exopolymeric substances protect microorganisms from various environmental stresses. Exopolymeric substances have unique characteristics. Some of the functional properties of them include adhesion, aggregation, binding activity, energy and nutrient source, water retention, and sorption. One of the exopolymeric substances is fungal exopolymeric substances. The fungal exopolysaccharides are pullulan, scleroglucan, fungal ?-glucans, botryosphaeran, and others. The fungal exopolymeric substances are valuable products because of their different application areas such as industries of medical, cosmetic, food, wastewater treatment and agriculture. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.
Keywords: Agriculture; Exopolymeric substances; Fungal; Industry; Wastewater